Effect of cold wave on soil temperatures - BHANDARI, S. G.; KELKAR, R. R. (MAUSAM, 1984)
Intensive observations from surface to 150 cm depth of soil on clear days in January 1981 covering the period of moderate cold wave were recorded in black cotton soils at Pune. There was a little pr no .diurnal variation below 30 cm: During the passage of cold wave upper layers of soil responded quickly and appreciable fall of temperatures were noticed. Persistence of moderate cold wave conditions for about two days influenced the deeper depths temperatures too. Partial clouding mainly affected the temperatures of surface and 5 cm. Thermal diffusivity within surface to 5 cm was 0.1029X 10-9 cm2/sec while that in 15 to 20 cm was 0.3043x10-9 cm2/sec. Damping depth was found to be 7.6 cm. Both these parameters being low in comparison to those for sandy soils diurnal temperature wave dampens at faster rate in black cotton soils.